Reflexões acerca da pedagogia do futsal no ambiente universitário: análises a partir do discurso do sujeito coletivo - DAMBROS, Gabriel (2014)
Sport is a patrimony of humanity and, as such, integrates the activities developed at a University. Faced With questions related to the role that sport represents at the Brazilian’s University, we investigated different aspects related to this theme. The subject of this study consists in unveiling the sport in the university environment and its relationship with the role of the coach as facilitator of the process of teaching and learning futsal modality, as means of representation competitive university. The research was composed of a case study, through a qualitative, using as an instrument interviews. Composed of open questions, aiming at the exploration of thought in the answers, the subjects interviewed were the players of the futsal teams, the managers of the University chosen and an ex-coach of modality, all being involved with the development of the sport. For the analysis of the results we use the technique of the Collective Subject Discourse, proposed by Lefevre and Lefèvre (2003). We found that the speeches of players highlight the value of sport in the University as educational activity; reveal important aspects for the development of competitive representation teams; and suggest that the ideas defended by the Pedagogy of Sport consist of guidelines for guiding the development of pedagogical actions promoted by the coaches. The managers and ex-coach indicate that sport can contribute to the students education, as also pointed out the absence of a institutional political project to tow the sport as a means to assist the students formation. In the opinion of this researcher, the information found revealed many inconsistencies between the discourses and the reality of the development of the sport in this University. In the analyzed speeches, it was possible to identify that the University researched presents a relevant work for the sport university, however, did not identify the sport activity as an integral part of the formative project offered by the institution, a fact that complicate the actions by professionals in Physical Education present in University.